Towards an Integrated Model of Educational System Evaluation: The Role of Educational Inspection - Estefanía Lera, José Luis (Avances en Supervisión Educativa, 2023)
The need to move towards an integrated model of educational system evaluation is proposed, involving the various actors participating, from the administration to the educational community, in a way that recognizes, coordinates, and works more collaboratively so that the system gains in effectiveness and efficiency and can face the weak points detected in its operation with a more realistic and contextualized diagnosis. The contribution made by the different actors in the evaluation of the system at the macro, meso, and micro levels is analyzed, and proposals are made to move towards an integrated model of shared responsibilities, including, among others, the creation of a “School Evaluation Council” as a body attached to the Ministry of Education, Vocational Training, and Sports, which coordinates, guides, and promotes an evaluation policy of the system that impacts on institutional self-assessment and the external evaluation of centers. The educational inspection, as one of the actors participating in the system evaluation, due to its evaluative function and the strategic place it occupies, is a key factor of interconnection between the different elements.